§ 119: Give Me Liberty or Give Me Death! - Gildenhard, Ingo (Open Book Publishers, 2018)
Cicero clinches the account with his public service — and a twin focus on liberty and death. The final thought (or wish) of Philippic 2 is one of cosmic justice: that the fate of the individual reflects the nature of his actions within the public sphere. Those who invested much in the commonwealth ought to see their efforts rewarded; those who harmed the civic community ought to suffer accordingly. Much to Cicero’s regret, reality proved recalcitrant to this principle: throughout much of his career,...